Training, detraining and bone effect of exercise on bone mass and structure with special reference to maintenance of the exercise induced bone gain - Kontulainen, S. (2002)
The objectives of this thesis were to investigate the effects of long-term mechanical loading on mass, size and mechanical strength of bone in male and female racquet sports players and to evaluate the maintenance of exercise-induced bone gain in these players during the following years of reduced training. In addition, bone maintenance was assessed after jumping exercise interventions in pubertal girls and premenopausal women. Altogether 223 subjects were involved in the study serie. The cross-sectional comparisons of bone mass, structure and strength between playing and nonplaying arm of racquet sports players showed that playing had increased bone size but not volumetric density of cortical bone. The loaded bone shaft seemed to have grown periosteally leading to 11-34% greater estimated bone strength in the loaded arm compared to its counterpart. In female players, this exercise-induced benefit in bone strength was more than two times greater if starting age of the activity had been before the onset of puberty. Prospective 4- and 5-year follow-up studies of male and female racquet sports players and their controls revealed that despite reduced training the exerciseinduced bone gain was well maintained in all groups of players regardless of the starting age of activity (either in growing years or in adulthood) and different amount of exercise-induced bone gain. Changes in training were weakly related to the changes in the side-to-side BMC difference even among players who had completely stopped training a minimum one year before the follow-up. As regards, the maintenance of the effects of jumping interventions on bone and physical performance were evaluted in perimenarcheal girls and in premenopausal females. Girls` follow-up showed that although the greatest proportion of bone mineral accrual was attributable to growth, an additional bone gain achieved by jumping training was maintained at the lumbar spine at least a year after the end of the training. In premenopausal women, the significant bone gain that was obtained by 18-month high-impact exercise was well maintained three and half years after the end of the intervention, while the exercise-induced improvements in the neuromuscular performance had returned to the baseline level. All these findings emphasise long-term benefits of exercise on bone. Therefore, exercise can be recommended for preventing osteoporosis and related fractures.